A disrupted RNA editing balance mediated by ADARs (Adenosine DeAminases that act on RNA) in human hepatocellular carcinoma. Issue 5 (13th June 2013) - Chan, Tim Hon Man; Lin, Chi Ho; Qi, Lihua; Fei, Jing; Li, Yan; Yong, Kol Jia; Liu, Ming; Song, Yangyang; Chow, Raymond Kwok Kei; Ng, Vanessa Hui En; Yuan, Yun-Fei; Tenen, Daniel G; et al.
Abstract : Objective: Hepatocellular carcinoma (HCC) is a heterogeneous tumour displaying a complex variety of genetic and epigenetic changes. In human cancers, aberrant post-transcriptional modifications, such as alternative splicing and RNA editing, may lead to tumour specific transcriptome diversity. Design: By utilising large scale transcriptome sequencing of three paired HCC clinical specimens and their adjacent non-tumour (NT) tissue counterparts at depth, we discovered an average of 20 007 inferred A to I (adenosine to inosine) RNA editing events in transcripts. The roles of the double stranded RNA specific ADAR (Adenosine DeAminase that act on RNA) family members (ADARs) and the altered gene specific editing patterns were investigated in clinical specimens, cell models and mice. Results: HCC displays a severely disrupted A to I RNA editing balance. ADAR1 and ADAR2 manipulate the A to I imbalance of HCC via their differential expression in HCC compared with NT liver tissues. Patients with ADAR1 overexpression and ADAR2 downregulation in tumours demonstrated an increased risk of liver cirrhosis and postoperative recurrence and had poor prognoses. Due to the differentially expressed ADAR1 and ADAR2 in tumours, the altered gene specific editing activities, which was reflected by the hyper-editing of FLNB (filamin B, β) and the hypo-editing of COPA (coatomer protein complex, subunit α), are closely associated with HCC pathogenesis. In vitro and in vivo functional assays prove that ADAR1 functions as an oncogene while ADAR2 has tumour suppressive ability in HCC. Conclusions: These findings highlight the fact that the differentially expressed ADARs in tumours, which are responsible for an A to I editing imbalance, has great prognostic value and diagnostic potential for HCC.